2014
DOI: 10.1093/hmg/ddu298
|View full text |Cite
|
Sign up to set email alerts
|

Tuning intracellular homeostasis of human uroporphyrinogen III synthase by enzyme engineering at a single hotspot of congenital erythropoietic porphyria

Abstract: Congenital erythropoietic porphyria (CEP) results from a deficiency in uroporphyrinogen III synthase enzyme (UROIIIS) activity that ultimately stems from deleterious mutations in the uroS gene. C73 is a hotspot for these mutations and a C73R substitution, which drastically reduces the enzyme activity and stability, is found in almost one-third of all reported CEP cases. Here, we have studied the structural basis, by which mutations in this hotspot lead to UROIIIS destabilization. First, a strong interdependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Understanding the mechanisms by which disease‐associated mutations affect protein stability and function, as well as the effects of second‐site suppressor mutations may help to guide the development of novel therapeutic strategies aimed at treating inherited diseases . In this work, we provide a detailed mechanism that unifies the inactivation caused by P187S and its rescue by H80R in the context of a FAD binding mechanism in which ligand binding is strongly coupled to the conformational transition between binding competent and noncompetent states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the mechanisms by which disease‐associated mutations affect protein stability and function, as well as the effects of second‐site suppressor mutations may help to guide the development of novel therapeutic strategies aimed at treating inherited diseases . In this work, we provide a detailed mechanism that unifies the inactivation caused by P187S and its rescue by H80R in the context of a FAD binding mechanism in which ligand binding is strongly coupled to the conformational transition between binding competent and noncompetent states.…”
Section: Discussionmentioning
confidence: 99%
“…K CONF stands for the equilibrium constant between noncompetent and competent states in the absence of ligand and K FAD for the FAD (intrinsic) equilibrium association constant to competent states, while these two constants are related to the overall (apparent) affinity through the expression: K FAD(app) = K FAD /1 + K CONF [22]. [17,26]. In this work, we provide a detailed mechanism that unifies the inactivation caused by P187S and its rescue by H80R in the context of a FAD binding mechanism in which ligand binding is strongly coupled to the conformational transition between binding competent and noncompetent states.…”
Section: Discussionmentioning
confidence: 99%
“…This experimental evidence suggested that some of the UROS defects alter the catalytic machinery of the enzyme, other mutations impair the stability of the folded conformation, whereas others affect both the protein activity and stability (Table SII). More recent works about the UROS C73R mutation demonstrated that the apparent enzyme activity was reported to decrease over time at a rapid rate due to premature unfolding and quick degradation resulting in undetectable protein levels in the cell (Fortian et al , ; ben Bdira et al , ). Also the P248Q mutant was associated with a reduced kinetic stability and this could also be valid for the other missense mutations (Blouin et al , ).…”
Section: Genetic Basesmentioning
confidence: 99%
“…Experiments in both human cell lines and a murine model have shown that the protein is rapidly eliminated, via the proteosomal instead of the lysosomal pathway (Fortian et al, 2011;Blouin et al, 2013). However additional degradation pathways acting on the eukaryotic intracellular homeostasis of this enzyme have also been suggested (ben Bdira et al, 2014).…”
Section: Biochemical Backgroundmentioning
confidence: 99%
“…The genetic defect is most commonly in the gene encoding UROS enzyme in an autosomal recessive manner, and rarely in the GATA1 gene as an X-linked manner. CF3R mutation of the UROS gene is accounting for 20% of the reported mutations in CEP [3].…”
Section: Introductionmentioning
confidence: 99%